Mechanochromic fluorescence in epoxy as a detection method for barely visible impact damage in CFRP composites. (8th February 2017) - Toivola, Ryan; Lai, Po-Ni; Yang, Jeffrey; Jang, Sei-Hum; Jen, Alex K.-Y.; Flinn, Brian D.
Abstract: The demand for carbon fiber reinforced epoxy as a structural material has greatly increased recently, especially in aerospace and commercial aircraft applications. The need for accurate detection of barely visible impact damage (BVID) in these materials is increasing as well. The relatively unexplored field of mechanochemistry (and its sub-field mechanochromism) offers attractive methods of detecting impact damage, if the materials involved have adequate properties for aerospace applications. With this in mind, we have observed mechanochromic behavior in a little-used combination of epoxy and amine curing agent - tetraglycidyl-4′-4 diaminodiphenylmethane with diethylenetriamine - that produces strong fluorescence in response to compression and impact. The mechanochromic fluorescence is detectable at ∼0.5 GPa, and visible at ∼1.0 GPa, and shows consistent increase with increasing true stress. The fluorescence intensity decreases over time; the decrease follows a decay pattern suggesting that the emission comes from a mechanochemically formed radical species which gradually recombines into a non-fluorescent species. The mechanochromic epoxy system has processing flexibility and can be spray coated onto parts; these coatings activate due to impacts and indentations consistent with BVID events, showing the system's potential as a non-destructive evaluation material and method for composite structures.